2021
DOI: 10.1111/ijcp.14701
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antimicrobial resistance pattern among patients with sepsis: A retrospective cohort study

Abstract: Sepsis is a systemic infection defined as "life-threatening organ dysfunction caused by a dysregulated host response to infection". "Septic shock is a subset of sepsis with circulatory and cellular/ metabolic dysfunction associated with a higher risk of mortality" by sepsis surviving campaign (SSC). 1 The sepsis and septic shock burden on healthcare is extensive, estimated according to the recent publication in 2017 as 48.9 million cases and 11 million sepsis-related deaths worldwide, accounting for 19.7% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Thus, some indicators are needed to evaluate the clinical outcome. Previous investigations revealed that indicators like procalcitonin (PCT), age, intensive care unit (ICU) stay, malignancy, resistant bacterial infection, stroke, sex, diabetes mellitus, chronic renal failure, and previous use of antibiotics could indicate a poor prognosis of bloodstream infection ( Zhang et al., 2019 ; Blanchard et al., 2020 ; Barlas et al., 2021 ; Chen et al., 2021 ; Jain et al., 2021 ; Zduniak et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some indicators are needed to evaluate the clinical outcome. Previous investigations revealed that indicators like procalcitonin (PCT), age, intensive care unit (ICU) stay, malignancy, resistant bacterial infection, stroke, sex, diabetes mellitus, chronic renal failure, and previous use of antibiotics could indicate a poor prognosis of bloodstream infection ( Zhang et al., 2019 ; Blanchard et al., 2020 ; Barlas et al., 2021 ; Chen et al., 2021 ; Jain et al., 2021 ; Zduniak et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 Jain ve arkadaşları tarafından sepsis hastaları üzerinde yapılan bir çalışmada ise %32.8 oranında KNS'ler kan kültüründe tespit edilmiştir. 25 Bizim çalışmamızda da büyük çoğunlukla kan örneklerinde tanımladığımız KNS'lerin içinde S. haemolyticus türünün yaygınlığındaki artış dikkate alındığında bu patojene yönelik uygun tanı ve yönetim politikalarının üretilmesinin doğru bir yaklaşım olacağı görüşündeyiz. Ayrıca 2019 yılına göre KNS'lerin izolasyon sıklığında gözlemlediğimiz azalmanın 2020 ve 2021 yılında artan idrar örneklerine bağlı olarak üriner patojen izolasyon artması sonucu oluşan görece bir durum olduğunu düşünmekteyiz.…”
Section: Discussionunclassified